2017
DOI: 10.11114/jets.v5i2.2062
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Fourth Grade Primary Students’ Reader Self-perceptions in Terms of Gender and Preschool Educational Background

Abstract: The aim of this study was to analyse perceptions of fourth grade primary school students on their reading ability. In the study, screening model was used as a quantitative research method. The sample of this research was selected by convenience sampling. The sample consisted of 556 fourth grade students who received education in 8 public schools in 2014-2015 academic year in Tuzla, Pendik, Çekmeköy and Kadıköy districts, in İstanbul. A 'personal information form' and a 'Reading Self-Perception Scale' were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Based on the results of the present study examining the relationship between primary school students' reader self-perception levels and reading comprehension skills, it seems clear that students' total scores in the reader self-perception scale show significant differences in favour of female students when the gender variable is taken into account. In the literature, Baker and Wigfield (1999), Baştuğ and Çelik (2015), İnnalı and Aydın (2014), Meece et al (2006), Sağırlı and Okur (2017), Yaylı and Duru (2008), Phillips (2002) and Ünal (2012) reported a similar result and concluded that female students' reader self-perception levels were higher than those of male students. Still, there are also studies (Byrne, 1986;Karakoç-Öztürk, 2015) that found that the reader self-perception did not change according to gender.…”
Section: Conclusion and Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Based on the results of the present study examining the relationship between primary school students' reader self-perception levels and reading comprehension skills, it seems clear that students' total scores in the reader self-perception scale show significant differences in favour of female students when the gender variable is taken into account. In the literature, Baker and Wigfield (1999), Baştuğ and Çelik (2015), İnnalı and Aydın (2014), Meece et al (2006), Sağırlı and Okur (2017), Yaylı and Duru (2008), Phillips (2002) and Ünal (2012) reported a similar result and concluded that female students' reader self-perception levels were higher than those of male students. Still, there are also studies (Byrne, 1986;Karakoç-Öztürk, 2015) that found that the reader self-perception did not change according to gender.…”
Section: Conclusion and Discussionmentioning
confidence: 82%
“…In this sense, it seems that whether or not students comprehend what they read is not influenced by whether or not they consider themselves as a competent reader. However, it has often been suggested that individuals who can regard themselves as competent in terms of the reader self-perception will have higher reading comprehension skills (Henk & Melnick, 1995;Sağırlı & Okur, 2017). The fact that there is a weak, negative and significant correlation between reading comprehension skills and attitudes towards reading in the 2 nd grade students shows that students with a positive attitude towards reading have a low level of reading comprehension or those with a negative attitude towards it have a high level of reading comprehension.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, limited opportunities for recruitment resulted in the relatively small analysis sample. Secondly, the RSPS2 was originally designed for use with native speakers although it has been used with L2 learners in other contexts (Alrwele 2015;Sağırlı and Okur 2017 The results presented here can help us recognize that ER can alter L2 readers' internal physiological states while reading and allow them to experience more positive emotions connected to reading in the target language. Thus, these findings…”
Section: Resultsmentioning
confidence: 96%